Agricultural Extension Innovation: Preparation of Booklets and Youtube Videos on Crystal Guava Pests and Diseases - Nur Rokhimah Hanik; Tri Wiharti; Anwari Adi Nugroho; Agus Purwanto (Postgraduate, University of Mataram, 2025)
In the digital era, it is necessary to develop an online booklet on crystal guava pests and diseases. Pests and diseases are major constraints on agricultural productivity, disrupting plant physiology and growth, and thus reducing yields. The objective of this research is to develop an online booklet on crystal guava pests and diseases and how to manage them. Data collection was conducted through observation and interviews with owners and managers to obtain information on pests and diseases. Data were analyzed using descriptive qualitative methods. The study identified five pests of crystal guava: fruit fly (Bactrocera dorsalis), ladybug (Epilachna admirabilis), leaf caterpillar (Lepidoptera: Pyralidae), armyworm (Spodoptera litura), and mealybug (Paracoccus marginatus). The diseases identified were: Capnodium citri fungus (sooty mold), anthracnose disease (Colletotricum sp), red rust disease (Chephaleuros virescens), white fungus Fusarium sp, fruit rot disease (Botryodiplodia sp), and leaf spot disease (Cercospora psidii). Crystal guava care is carried out by maintaining garden cleanliness, adjusting plant spacing, fertilizing, spraying insecticides, setting fly traps, and wrapping young fruit. The conclusion of this research can be developed into a YouTube-based booklet as a guide for crystal guava farmers.